Generational Differences in Awareness and Eco-friendly Behavior among Women towards Household Waste Management with a Special Focus on AHP Waste - Hina Samreen; Dr. Falak Shad Memon; Dr. Hira Mujahid (Indus Journal of Social Sciences, 2025)
Effective household waste management is crucial for addressing the challenges that arise from rapid urbanization. An increase in awareness of the environmental issues related to careless waste disposal, and a clear sense of responsibility for responsible resource use, waste segregation, and sustainable disposal practices at the household level may help to address the environmental impacts of household waste. Understanding the importance of awareness in describing human actions and eco-friendly behaviour, this study investigates the generational differences among women—across Generations X, Y, and Z. Data for 388 female respondents, grouped into 3 Generations is gathered through a convenience sampling method. The 16-item questionnaire, addressing awareness, concern for the environment and responsibility was analyzed using the non-parametric KWS test. The study summarizes the positive attitudes of younger generations towards careful waste disposal, waste segregation practices and intention to save natural resources.